(untitled) (Forum Theologicum Sardicense, 2025)
The present paper gives an overview of the Medieval Bulgarian translations of St. Athanasius’ Against the Arians. It analyses the historical and pastoral reasons of the Ecumenical Patriarchate to promote this text in the Bulgarian milieu of the 10th century.